A systematic review on the prevalence and assessment of persons with a diagnosis of personality disorders in outpatient forensic mental health services - van Reijswoud, Barbera (The journal of forensic psychiatry & psychology, 2025)
Persons with a diagnosis of personality disorders (PDs) are associated with increased risk of violent and antisocial behavior and with higher recidivism risk and are therefore treated in outpatient forensic mental health settings (OFMH). There are promising results for treatment of people with the diagnosis of PD in this setting. However, information on prevalence and assessment seems scarce. This systematic review focuses on the prevalence of diagnoses of PDs in general and diagnoses of specific PDs in OFMH, and how assessment was done. Following the PRISMA protocol, five electronic bibliographic databases were searched. This yielded 251 records of which eight studies on prevalence and nine on assessment were included in the review. Because of the many differences between these studies and the settings studied, prevalence rates varied widely and no single percentage of diagnosis of PDs in OFMH settings can be given. Moreover, there appeared to be no commonly used or preferred method of assessment; clinical assessment, structured interviews and self-report questionnaires were all used, while few studies used validity scales or a control for response styles. Patients and practitioners in OFMH may benefit from knowledge of prevalence rates and proper assessment of diagnosis of PDs. This requires new research.